Evaluation of Covid-19 anti-spike IgG antibody five months after the second Covid-19 vaccination - Rafie, Reyhaneh Alipoor; Azimi, Leila; Armin, Shahnaz; Aghamohammadi, Amirali; Karimi, Abdollah; Fallah, Fatemeh; Khodaei, Hannan; Mansour Ghanaie, Roxana; Alebouyeh, Masoud (German Medical Science GMS Publishing House, 2023)
Background: Studies in different communities have shown significant differences in IgG antibody titers in the time period after the first and second doses of the vaccines. This study aimed to serologically evaluate the IgG anti-spike antibody titer five months after injection of the second COVID-19 vaccine in healthcare workers.Materials and method: This study was performed in healthcare personnel for whom five months had passed since their second anti-Covid-19 vaccination. The level of IgG antibody against SARS-CoV-2 spike protein was measured by ELISA. Healthcare workers in Mofid Children's hospital received three brands of vaccines: Sputnik V, Sinopharm, and AstraZeneca.Results: The mean titer of anti-spike IgG was 4.3±2.29 units. The percentage of positive cases of the antibody was estimated to be 96.4%. The titer of anti-spike IgG antibody was dependent on both the occupational area and a positive history of Covid-19 disease.Conclusion: About 96.4% of the staff vaccinated against Covid-19 had a high titer of anti-spike IgG antibody even five months after inoculation of the second dose. The field of occupational can affect the level of antibody present